HealthAware: An Advice System for Stress, Sleep, Diet and Exercise - Sano, Akane; Johns, Paul; Czerwinski, Mary (ACII 2016: Affective Computing and Intelligent Interaction, 2015 International Conference on, 2015)
We developed a feedback-loop, user-tailored advice system to provide stress interventions and advice about improving sleep, diet, and exercise habits at the workplace. Thirty participants joined a 2 week study: in the first week, we collected their behaviors about sleep, diet, exercise and stress levels using Fitbit and surveys. During the second week we continued monitoring, and based on the participants’ measurements in the previous days, we also provided interventions and advice during the workday, and evaluated their preferences. We found that participants with higher stress levels liked stress interventions more and that somatic activities were most preferred and reduced stress levels the most. We observed individual preference differences in the types of advice; however, tracking and receiving advice raised users’ awareness of their stress, sleep, exercise, and dietary behaviors. We found that the largest positive impact was on our participants’ dietary behaviors.